An appraisal and critique of land redistribution approaches in South Africa - Phiri, M C S (Rhodes University, Faculty of Humanities, Department of Sociology, 2020)
This paper is in response to the PLAAS Land Conference held in February 2019 which aimed at discovering an alternative to how to solve the land question. The conference came at a time where land and agrarian reform re-emerged in South African socio-policy discussion. After twenty-five years of democracy the three land reform programmes have failed to restructure apartheid's economic segregation, exclusionary land ownership patterns and to restore dignity to poor black South Africans. This study offers a detailed examination of the discourse of South African land reform, specifically the redistribution component with a focus on the land redistribution approaches presented at the PLAAS conference. Ultimately, the study puts forward a synthesized land redistribution approach as a hybrid solution to the land and agrarian crisis.
Keywords: University of the Western Cape. Institute for Poverty, Land and Agrarian Studies; Land reform -- South Africa; Land reform -- Law and legislation -- South Africa; Agriculture and state -- South Africa; Reconstruction and Development Programme (South Africa); Land reform beneficiaries -- South Africa; South Africa -- Economic conditions -- 1991-; South Africa -- Social conditions -- 1994-; South Africa -- Economic policy; Land tenure -- Law and legislation -- South Africa; Black people -- South Africa -- Economic conditions; Black people -- South Africa -- Social conditions